Human and Machines Philosophical Thinking of Artificial Intelligence - Gu, Jun.; Guo, Yike. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book shares Chinese scholars' philosophical views on artificial intelligence. The discussions range from the foundations of AI-the Turing test and creation of machine intelligence-to recent applications of AI, including decisions in games, natural languages, pattern recognition, prediction in economic contexts, autonomous behaviors, and collaborative intelligence, with the examples of AlphaGo, Microsoft's Xiao Bing, medical robots, etc. The book's closing chapter focuses on Chinese machines and explores questions on the cultural background of artificial intelligence. Given its scope, the book offers a valuable resource for all members of the general public who are interested in the future development of artificial intelligence, especially from the perspective of respected Chinese scholars.
Does the Turing test work? -- How does machine intelligence emerge? -- By wining at Go, can machines really surpass human beings? -- What makes Robot Xiaobing's works poetic? -- Will diagnosing Robot Make Real Doctors Out of Work? -- Will the Robot's Dominance of the Stock Market Disrupt the Market Order? -- How Can AI and Robots Go Hand in Hand? .
Keywords: Artificial intelligence; Technology; History; Technology-Philosophy.; Computers and civilization; Computational intelligence; Artificial Intelligence; History of Technology; Philosophy of Technology; Computers and Society; Computational Intelligence